الإشاريات وأبعادها التداولية في القصص القرآني: قصتا موسى ومريم أنموذجاً: The Deictics and Their Pragmatic Dimensions in Quranic Narratives: The Stories of Moses and Mary as a Case Study - Ridwanulahi Akorede Uthman,; Asem Shehadah Ali, (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث تعدُّ الإشاريات عنصراً مهماً من عناصر النظرية التداولية، فهي أساسية من حيث وظيفتها النحوية والدلالية، عليها يقوم طرفا الخطاب، وبها نعرف الإطار الزماني والمكاني للخطاب، والإشاريات من علامات لغوية، لا يتحقق مقصدها إلا عند السياق التداولي؛ لأنها مبهمة لا معنى لها؛ حيث إنها ترتبط بمراجع غير ثابتة، وقد بني هذا البحث على إشكالية مفادها كيف تتجلى وتكتشف الإشاريات في قصتى موسى ومريم عليهما السلام؟ وأما الهدف في الدراسة فهو إبراز الإشاريات بأنواعها المتعددة في القصتين، وتكمن أهمية هذه الدراسة في أنها تتجسد فيها أنماط الإشاريات وعناصرها وأقسامها في قصتي موسى ومريم عليهما السلام، وقد اعتمد البحث على المنهج الوصفي والتحليلي في شرح وبيان أنواع الإشارية الكامنة في القصتين، وفي نهاية المطاف توصل الباحث إلى عدة نتائج، أهمها: أن الإشاريات في قصتي موسى ومريم متعددة ومتنوعة، فضلا عن دورها واسهامها في الترابط والتماسك والانسجام بين حوادث القصتين. ABSTRACT Deictics are an important element of pragmatics theory They are essential in terms of their grammatical and semantic function, as they serve as the foundation for the two parties in discourse, and through them, we understand the temporal and spatial framework of the discourse. Deictics are linguistic markers whose meaning is realized only in a pragmatic context, as they are vague and lack fixed references. This research is based on the problem of how deictics manifest and are uncovered in the stories of Moses and Mary (peace be upon them). The aim is to highlight the various deictic elements in the stories of Moses and Mary. The significance of this study lies in its demonstration of the patterns, elements, and types of deictics in these two stories. The research employed the descriptive and analytical method, and by the end of this study, the researcher arrived at several conclusions, the most important of which is that deictics in the stories of Moses and Mary are numerous and varied, contributing to the coherence, cohesion, and harmony between the events of the two stories.